Examining the Dominant Ideology in the History Curriculum: A Case Study of Lesotho’s Grade 9 History Syllabus - Atang Thulo (Universal Education, 2026)
This study analyses Lesotho’s Grade 9 History syllabus to identify the dominant curriculum ideology embedded within it. Using a qualitative case study approach and document analysis, the syllabus aims, assessment objectives, skills, and suggested learning experiences were examined through content analysis. The findings reveal that the syllabus is overwhelmingly dominated by the scholar-academic ideology, with limited representation of learner-centred and social efficiency ideologies, and an almost complete absence of social reconstruction elements. This ideological imbalance prioritises content transmission over critical engagement, practical application, and social transformation. Consequently, the syllabus shows limited alignment with Lesotho’s educational goals and 21st-century learning demands. The study recommends a more balanced integration of curriculum ideologies to enhance learner engagement, relevance, and the development of socially responsive and critically informed citizens.